Macrophomina phaseolina alters the biochemical pathway in Vigna radiata chastened by Zn2+ and FYM to improve plant growth. Issue 1 (1st January 2018) - Khan, Kashif Ali; Shoaib, Amna; Arshad Awan, Zoia; Basit, Abdul; Hussain, Mujahaid
ABSTRACT: Mung bean [ Vigna radiata (L.) Wilczek] is an important cash pulse crop extensively cultivated in the arid region of Pakistan, which encounters intimidating charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. The current research was conducted to check the potential of Zn (1.25, 2.44 and 5 mg kg −1 ) and FYM [farmyard manure (1% and 2%)] in mono-, bi- and trilateral interaction in managing disease and improving yield. Suppression of plant immunity by M. phaseolina was indicated by the change in activities of antioxidant enzymes (CAT and SOD) and cell wall strengthening enzymes (POX and PAL) that revealed inability of the protein receptor to identify the pathogen elicitor. FYM improved soil physicochemical properties and beneficial microbes activity, which released antimicrobial protein- and plant defense-stimulating protein and in response to ROS (reactive oxygen species) signaling molecules plant susceptibility was reduced. However, Zn as a co-factor chastened the ROS in stressed cells by upregulation of antioxidant enzymes in favor of the plant. The complex interaction of FYM and Zn potentially hijacked the further multiplication of pathogen. Finally, soil amendment improved biological attributes and grain yield to profitable farming in terms of harvest index percentage and benefit–cost ratio.